Effective Power and Speed of Mining Dump Trucks in Fuel Economy Mode - V. I. Alexandrov; M. A. Vasileva; V. Y. Koptev (Записки Горного института, 2019)
Existing methods for determining the effective power, based on the calculation of the average indicator operation of the engine during the piston stroke, do not take into account the change in thermodynamic parameters and the polytropic operation of the engine, the value of which depends on the polytropic efficiency of the duty cycle. This is the reason that the calculation of the effective power leads to some error – the margin of the engine features. The identification of this stock allows us to review the entire line of dump trucks in the direction of increasing their pass- port effective capacity, which will lead to a reduction in capital purchase costs due to the choice of a previously un- derestimated and cheaper option, as well as a reduction in current operating costs due to a decrease in the specific fuel consumption rate. Taking into account the stochastic nature of the transport process and assessing the influence of all external and internal factors when calculating the rational mode of operation of a mining truck can further reduce specific fuel consumption by choosing the rational speed of its movement in loaded and empty directions.